Lexical and grammatical cohesion analysis in “clouds” song lyrics - Dewi, Luh Gede Ayu Krisna Sari (Journal of Language, Literature, Social and Cultural Studies, 2023)
The objective of the study is to investigate and describe the lexical and grammatical devices as cohesion in Zach Sobiech's song "Clouds". The subject of the study is the lyrics of the "Clouds" song. The data was conducted by using qualitative description by following the techniques of the study. The data collected is about the lexical cohesion (repetition, a synonym, and antonym) and the grammatical cohesion (reference and conjunction) found in "Clouds" song lyrics. YouTube and earphones helped the writer in collecting data. The study exhibits the types of lexical and grammatical cohesion. It starts with repetition, synonym, antonym, the reference, and conjunction. The element that appears most in the data is the conjunction and the repetition.